The Relationship between Parenting Style and Career Decision Making Self-Efficacy in Undergraduates: Mediating Effect of Work Values - HOU, Yongmei; Runjia, Chen (Advances in Social Sciences Research Journal, 2022)
Objective To explore the characteristics of parenting style, work values and career decision making self-efficacy in undergraduates and analyze the relationship among the above 3 variables. Method: Eight hundred and forty-nine undergraduates were selected by stratified random sampling from 7 universities in Guangdong province. Short-Form Egna Minnen av Barndoms Uppfostran (s-EMBU), Work Values Scale for College Students (WVS) and Career Decision Making Self-Efficacy Scale (CDMSES) were administred to them. Results: ⑴ The score of parental control was at a low level; The scores of parental care, social promotion, ease and stability, salary and reputation, benifits and welfare, total scores and five dimensions of CDMSES belong to the medium level; The scores of the other 6 dimensions of WVS belong to high scores. ⑵ Purposeful values play a partial mediating role in the relationship between parental care and career decision making self-efficacy, and the mediating effect accounts for 33.9% of the total effect; Instrumental values play a partial mediating role in the relationship between parental care and career decision making self-efficacy, with the mediating effect accounting for 11.1% of the total effect; Work values play a partial mediating role in the relationship between parental care and career decision making self-efficacy, and the mediating effect accounts for 30.4% of the total effect. Conclusion: Parental care can not only directly predict college students’ career decision making self-efficacy, but also indirectly affect it through work values.